Zimbabwe opposition’s quest for electoral reforms in the post-GNU era: from Unity to action - Gift Mwonzora (Cogent Social Sciences)
The demand and clamour for electoral reforms in Africa are among one of the most pressing issues of today. Existing research has documented how citizens of several African countries have flooded the streets in anti-regime protests demanding electoral reforms from their respective governments. Less well researched, however, is how, (to what extent), and (with what) effect do opposition parties utilise collective action approaches in pushing for electoral reforms. By focusing on Zimbabwe, this article contributes to this relatively underexplored area by critically examining the motive, extent, strategies and collective action approaches utilised by the political opposition parties—specifically the Movement for Democratic Change Tsvangirai (MDC-T), later named the MDC-Alliance (MDC-A) in demanding electoral reforms post the Government of National Unity (GNU) era of 2009–2013. This entails exploring the efficacy of protest action, litigation, lobbying, petitioning, parliamentary debates and dialogue to spearhead and realise electoral reforms against an intransigent regime ahead of the 2018 harmonised elections in Zimbabwe. By drawing on documentary analysis of primary and secondary literature, interviews with party elites, and personal observations, the article established that it is challenging to realise wide-ranging electoral reforms in a context were bi-partisan interests are high and also in contexts were incumbents stand to benefit from an unreformed electoral system.